Actinomycosis manifested in the buccal mucosa estimated with scraping cytology: A case report. Issue 3 (May 2017) - Kouketsu, Atsumu; Matsui, Aritsune; Mori, Shiro; Saito, Haruka; Suzuki, Hikari; Shibahara, Yukiko; Kumamoto, Hiroyuki; Takahashi, Tetsu
Abstract: Actinomycosis, a rare chronic granulomatous bacterial infection induced by Actinomyces species, colonizes the mouth, colon, and vagina. Although Actinomyces spp. are well-known oral commensals, actinomycosis is a rare oral infection. It is difficult to detect Actinomyces in biopsies, using histopathologic methods, or through examination of bacterial cultures; therefore, providing an accurate diagnosis is problematic. Recently, oral brush scraping cytology has been performed for the diagnosis of premalignant and malignant lesions, but it is difficult to determine the efficacy of this method based on the published reports, and whether it is a suitable tool for detecting Actinomyces infections in the general public. Here, we report a rare case of actinomycosis of the buccal mucosa in an 8-year-old boy that was successfully diagnosed by scraping cytology. He exhibited pain and swelling in the left buccal, and was admitted to our hospital for emergency care. Clinical examination revealed pyrexia, tachycardia, trismus, ingestion disorder, lethargy, and ulcer as well as having an indurated mass in the left buccal mucosa accompanied by strong pain. Following a clinical diagnosis of acute phlegmon of the left buccal mucosa, antibiotic and fluid therapy was performed. Because of detection of Actinomyces colonies at the ulcer surface using scraping cytology, we continued to administer long-term antibiotic therapy with penicillin for 2 months. The patient's general condition was improved, and this was confirmed by laboratory results, and the trismus and painful nodular mass were successfully cured. The patient has shown no subsequent evidence of recurrence for 7 months of following treatment.